2011
DOI: 10.1016/j.neuron.2011.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Functional Specialization of Mouse Higher Visual Cortical Areas

Abstract: SUMMARY The mouse is emerging as an important model for understanding how sensory neocortex extracts cues to guide behavior, yet little is known about how these cues are processed beyond primary cortical areas. Here, we used two-photon calcium imaging in awake mice to compare visual responses in primary visual cortex (V1) and in two downstream target areas, AL and PM. Neighboring V1 neurons had diverse stimulus preferences spanning five octaves in spatial and temporal frequency. By contrast, AL and PM neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

51
528
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 404 publications
(587 citation statements)
references
References 85 publications
(155 reference statements)
51
528
8
Order By: Relevance
“…Our results for SF and TF tuning are similar to previous reports in V1 (Niell and Stryker, 2008;Gao et al, 2010;Van den Bergh et al, 2010;Andermann et al, 2011;Marshel et al, 2011). Two recent publications have investigated spatiotemporal tuning properties of PM (Andermann et al, 2011;Marshel et al, 2011). Their results parallel our observation of higher SF tuning in PM compared with V1.…”
Section: Distinct Spatiotemporal Frequency Tuning In V1 and Pmsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results for SF and TF tuning are similar to previous reports in V1 (Niell and Stryker, 2008;Gao et al, 2010;Van den Bergh et al, 2010;Andermann et al, 2011;Marshel et al, 2011). Two recent publications have investigated spatiotemporal tuning properties of PM (Andermann et al, 2011;Marshel et al, 2011). Their results parallel our observation of higher SF tuning in PM compared with V1.…”
Section: Distinct Spatiotemporal Frequency Tuning In V1 and Pmsupporting
confidence: 92%
“…Their results parallel our observation of higher SF tuning in PM compared with V1. It has also been reported that neurons in PM were significantly more tuned for speed than neurons in V1 and also preferred lower peak speeds (Andermann et al, 2011). On the contrary, we find the percentage of speed-tuned neurons to be lower in PM than in V1 and peak speed preferences to be highly overlapping although with a trend toward lower speeds in PM (Figs.…”
Section: Distinct Spatiotemporal Frequency Tuning In V1 and Pmsupporting
confidence: 55%
“…The OSI and DSI were calculated as described previously (34). In short, OSI was calculated as the maximum directional response, ΔR max , divided by the sum of responses in all other directions, ΣΔR other (0 ≤ OSI ≤ 1; 1 = perfectly orientation-tuned).…”
Section: Methodsmentioning
confidence: 99%
“…However, the actual functional properties of NFT-bearing neurons in intact neural circuits have not been explored previously (13). We addressed this question directly using awake in vivo two-photon calcium imaging in a mouse model of NFT formation (rTg4510) by applying recently developed imaging approaches allowing for single-neuron-level and population-level assessment of neural activity in awake mice (14). Because two-photon calcium imaging allows for measurement of response properties in many neurons simultaneously, we were able to directly isolate the impact of NFT deposition in a neuronal microcircuit by evaluating population-level network dynamics and, more specifically, by differentiating the function of individual NFT-bearing and neighboring non-NFT-bearing neurons.…”
mentioning
confidence: 99%
“…But the lesioning techniques used in these studies did not afford the spatial resolution for linking the behavioral deficit unequivocally to specific areas, a problem that will likely be overcome by optogenetic approaches (Lien and Scanziani 2013). Recently, significant progress was made by two-photon imaging of calcium transients in upper layer neurons of multiple areas in mouse visual cortex (Andermann et al 2011;Marshel et al 2011;Roth et al 2012). These recordings showed that tuning to high spatial frequency was more common in LI than in AL, RL and AM, which are more selective for high temporal frequency and the direction of motion.…”
Section: Dorsal and Ventral Processing Streamsmentioning
confidence: 99%